Model pembelajaran market place activity digital dalam meningkatkan minat belajar siswa di Sekolah Menengah Pertama - Syarifah, Alfiatus; Hasan, Nor (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The Digital Market Place Activity model is an innovative learning model that adapts the concept of buying and selling knowledge to increase student interaction, participation, and learning motivation. This study aims to analyze the effect of using the Digital Market Place Activity learning model on the interest in learning Islamic Religious Education (PAI) of eighth-grade students of SMP Negeri 1 Pademawu Pamekasan. The research method used is a quantitative approach with 31 students as respondents. Data were collected through a questionnaire based on two variables, namely the effectiveness of the learning model (X) and student learning interest (Y), then analyzed using descriptive statistics, validity and reliability tests, normality tests, Pearson Product Moment correlation tests, simple linear regression analysis, t-tests, and coefficient of determination (R²) tests with the help of IBM SPSS. The results showed that the data were valid, reliable, and normally distributed, with a correlation value of r = 0.662 and a significance of 0.000 <0.05, which means there is a positive and significant relationship between the two variables. The R² value of 0.439 indicates that 43.9% of student learning interest is influenced by the effectiveness of the Digital Market Place Activity model. Thus, this model has a positive and significant influence in increasing students' interest in learning Islamic Education subjects. Abstrak Model Market Place Activity Digital merupakan model pembelajaran inovatif yang mengadaptasi konsep jual beli pengetahuan guna meningkatkan interaksi, partisipasi, dan motivasi belajar siswa. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan model pembelajaran Market Place Activity Digital terhadap minat belajar Pendidikan Agama Islam (PAI) siswa kelas VIII SMP Negeri 1 Pademawu Pamekasan. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan jumlah responden sebanyak 31 siswa. Data dikumpulkan melalui angket berdasarkan dua variabel, yaitu efektivitas model pembelajaran (X) dan minat belajar siswa (Y), kemudian dianalisis menggunakan statistik deskriptif, uji validitas dan reliabilitas, uji normalitas, uji korelasi Pearson Product Moment, analisis regresi linier sederhana, uji t, serta uji koefisien determinasi (R²) dengan bantuan IBM SPSS. Hasil penelitian menunjukkan bahwa data valid, reliabel, dan berdistribusi normal, dengan nilai korelasi r = 0,662 dan signifikansi 0,000 < 0,05, yang berarti terdapat hubungan positif dan signifikan antara kedua variabel. Nilai R² sebesar 0,439 menunjukkan bahwa 43,9% minat belajar siswa dipengaruhi oleh efektivitas model Market Place Activity Digital. Dengan demikian, model ini berpengaruh positif dan signifikan dalam meningkatkan minat belajar siswa pada mata pelajaran PAI.